The inscription kept at King Narai National Museum Storage: The assumption on its source and new proposal on the Vasantatilakā metre and the word “gaṇapateḥ” - Wapeekunlaset, Phramaha Kaweesak (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 13 No 2 (2021): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
The inscription kept at King Narai National Museum Storage was written in Sanskrit, inscribed with Pallava script and dated around the 6th century. It was a stone fragment, preserved at King Narai National Museum Storage, Lopburi province. Its exact source was unknown, as it was donated to the museum by the villagers of Phetchabun province. It was read and translated by fine arts department in 2016. This article aims to present the assumption on its source. Then, it was found that the inscription probably originated from the ancient city of Si Thep, as its script was very similar to Si Thep 5 inscription. Then, there was the new proposal on the composition with Vasantatilakā metre and the word “gaṇapateḥ”, which may means (1) the leader of a troop, (2) Bṛhaspati, (3) Indra, (4) Śiva, or (5) Gaṇeśa.